“Fresh meat”: First year female students negotiating sexual violence on campus residences - Anderson, B.; Naidu, C. (South African Journal of Higher Education, 2022)
Abstract This article focuses on first-year black female students at the University of KwaZulu-Natal who were exposed to and experienced sexual violence. The aim of the study was, broadly, to determine how female students experience and negotiate gender, sexuality and violence in campus residences. Semi-structured individual interviews were utilised to generate data. The findings show that violence was shaped by gender and power dynamics. These students were first years, and predominantly from poor backgrounds, and therefore particularly vulnerable to sexual violence and unequal relationships. Alcohol, substance abuse and dangerous masculinised spaces further exacerbated their vulnerability. Poverty, scarce resources and gender intersect to produce vulnerability and constrained forms of their agency that translate into transactional relationships. The findings also suggest that being first year female students have implications for how these young women negotiated their newfound freedom away from the parental gaze. The study highlights the ways in which these first-year students are aware that sexual violence is prevalent on campus particularly in certain spaces such as Dark City and residence rooms. Members of the SRC and DSRA are cited as likely perpetrators of sexually predatory behaviours. We therefore propose that the Gender Based Violence Policy at UKZN should be introduced to first year students by way of induction courses, and that these courses should also include gender and sexuality education to help ensure that awareness around gender violence permeates the lives of all students.